Genome-wide investigation of the heat shock transcription factor (Hsf) gene family in Tartary buckwheat (Fagopyrum tataricum) - Moyang Liu; Qin Huang; Wenjun Sun; Zhaotang Ma; Li Huang; Qi Wu; Zizhong Tang; Tongliang Bu; Chenglei Li; Hui Chen (BMC Genomics, 2019)
Abstract Background Heat shock transcription factor (Hsfs) is widely found in eukaryotes and prokaryotes. Hsfs can not only help organisms resist high temperature, but also participate in the regulation of plant growth and development (such as involved in the regulation of seed maturity and affects the root length of plants). The Hsf gene was first isolated from yeast and then gradually found in plants and sequenced, such as Arabidopsis thaliana, rice, maize. Tartary buckwheat is a rutin-rich crop, and its nutritional value and medicinal value are receiving more and more attention. However, there are few studies on the Hsf genes in Tartary buckwheat. With the whole genome sequence of Tartary buckwheat, we can effectively study the Hsf gene family in Tartary buckwheat. Results According to the study, 29 Hsf genes of Tartary buckwheat (FtHsf) were identified and renamed according to location of FtHsf genes on chromosome after removing a redundant gene. Therefore, only 29 FtHsf genes truly had the functional characteristics of the FtHsf family. The 29 FtHsf genes were located on 8 chromosomes of Tartary buckwheat, and we found gene duplication events in the FtHsf gene family, which may promote the expansion of the FtHsf gene family. Then, the motif compositions and the evolutionary relationship of FtHsf proteins and the gene structures, cis-acting elements in the promoter, synteny analysis of FtHsf genes were discussed in detail. What’s more, we found that the transcription levels of FtHsf in different tissues and fruit development stages were significantly different by quantitative real-time PCR (qRT-PCR), implied that FtHsf may differ in function. Conclusions In this study, only 29 Hsf genes were identified in Tartary buckwheat. Meanwhile, we also classified the FtHsf genes, and studied their structure, evolutionary relationship and the expression pattern. This series of studies has certain reference value for the study of the specific functional characteristics of Tartary buckwheat Hsf genes and to improve the yield and quality of Tartary buckwheat in the future.